Attitude, knowledge and behaviour towards evidence‐based medicine of physical therapists, students, teachers and supervisors in the Netherlands: a survey. Issue 4 (29th November 2011) - Scholten‐Peeters, Gwendolijne G. M.; Beekman‐Evers, Monique S.; van Boxel, Annemiek C. J. W.; van Hemert, Sjanna; Paulis, Winifred D.; van der Wouden, Johannes C.; Verhagen, Arianne P.
Abstract Rationale, aims and objectives Evidence‐based medicine (EBM) has gained widespread acceptance in physical therapy. However, because little is known about the attitudes, knowledge and behaviour of physical therapists towards EBM, and their participation in research to generate EBM, we explored these aspects among physical therapy students, teachers, supervisors and practising physical therapists. Methods This is a cross‐sectional survey in which participants completed a web‐based questionnaire to determine their attitudes, knowledge and behaviour regarding EBM, and their participation in research. Results Questionnaires were sent to 814 participants of which 165 were returned. The overall mean score for attitude was 4.3 [standard deviation (SD) 1.0; range 1–7], which indicates a weak positive attitude. Teachers scored the highest (4.9, SD 1.2) and students the lowest (4.1, SD 0.8). Although most participants had some understanding of the technical terms used in EBM, only teachers felt able to explain these terms to others. Of the students, 45% rated their perceived EBM knowledge as bad and 45% as average, whereas 78% of the teachers considered that they had good knowledge. To answer clinical questions, most students generally use textbooks (96%) and the opinion of their supervisors (87.7%). Conclusions There is a weak positive attitude of physical therapists, teachers, supervisors and students towards participating in research in general practice, but there is a lack of knowledge and active behaviour regarding EBM, especially among physical therapy students.